Belgian football - Dejonghe, T.; Vandeweghe, H. (Journal of Sports Economics, 2006)
The Belgian football league declined, after the Bosman case, to a secondary level and became a "stepping stone" for players from outside the European Union. The transformation of professional football into a media-corporations-merchandising-markets model throughout Europe resulted in a decline of Belgian competition. The market in Belgian was too small to be competitive, and the old-fashioned Royal Belgian Football Association rejected adaptation to the new environment. Currently, clubs in Belgium can no longer compete with the European elite, and many small teams have been fighting for their existence year after year. The result is the increasing importation of inferior foreign players. A new phenomenon is that many clubs sell their players when they are sure of their prolongation in the first division.